Effect of ethyl acetate crude extract of Lasiodiplodia pseudotheobromae IBRL OS-64 against oral cavity bacteria with emphasis on Streptococcus mutans - Taufiq M.M.J, Darah I (Journal of Applied Pharmaceutical Science, 2019)
Streptococcus mutans and Streptococcus agalactiae have been reported in human oral diseases including caries and periodontitis. Thus, the present study was performed to investigate the effect of ethyl acetate crude extract of Lasiodiplodia pseudotheobromae IBRL OS-64, an endophytic fungus isolated from Ocimum sanctum leaf against S. mutans and S. agalactiae. Disk diffusion and broth microdilution assays were used to determine the antimicrobial activities with minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values. Meanwhile, the microscopic analysis was used to study the structural degeneration of bacterial cells. The fungal crude extracts demonstrated favorable antibacterial activity toward both test bacteria and produced an inhibition zone ranging from 16.0 to 21.2 mm. The MIC and MBC values of the fungal crude extract toward S. mutans and S. agalactiae were determined and the results showed that the MIC and MBC values were in the range of 125–500 μg/ml and 125–1,000 μg/ml, respectively. The time-kill study suggested that the ethyl acetate crude extract possessed bactericidal effect with concentration and time-dependent. Structural degeneration studies revealed the major abnormalities occurred to S. mutans cells after treated with the fungal crude extract where completed alterations of their morphology with the formation of cavities and collapsed cells beyond repair occurred. Therefore, the current study suggested the ethyl acetate crude extract of L. pseudotheobromae IBRL OS-64 could be an effective antibacterial agent to treat oral cavity bacteria.
Keywords: Streptococcus mutans, Streptococcus agalactiae, Lasiodiplodia pseudotheobromae, antimicrobial activities, microscopic analysis.